Analysis Of The Impact Of Carbon Tax And Green Property Tax On Jakarta's Local Revenue - Nurcahya, Wirawan Firman; Afandi, Muhamad; Faturrochman, Muhamad; Yaasiin, Thoha Hanif (WIM Solusi Prima, 2024)
Environmental issues are serious global challenges that must be addressed immediately. These issues require swift and appropriate action, including policies to support the transition to a greener economy. Carbon tax and green property tax are two fiscal instruments that the government can use to encourage environmentally friendly behavior and investment. This study aims to determine the effect of carbon tax and green property tax implementation on DKI Jakarta's regional income in an effort to implement the Green Economy in DKI Jakarta. The method used is descriptive qualitative with data collection techniques through literature studies. Data is sourced from the internet, including BPS, DKI Jakarta government website, and journals. The results showed that DKI Jakarta's regional income from carbon emission tax in 2023 reached Rp 837,210,000 with total gas emissions of 27,970 kiloton. The realization of green buildings in DKI Jakarta in 2023 exceeded the target, reaching 3.99 percent of the target of 2.5 percent, exceeding the target by 1.49 percent. Green property tax in the form of PBB deductions for green buildings is projected not to increase local revenue, but to reduce local revenue from taxes. However, this decrease in revenue is not significant, as the increase in green buildings will attract investors with a potential US30 billion green investment by 2030. This can be realized if buildings and companies in DKI Jakarta are green building certified. Reduced local revenue will be worth it if accompanied by reduced emissions from increased green buildings.